A FRAMEWORK FOR INTEGRATING FISCAL RISKS INTO THE ASSESSMENT OF REGIONAL FINANCIAL SECURITY - Shohzod Shavkatovich, Elmurodov («YANGI O’ZBEKISTON IQTISODIYOTI», 2026)
Fiscal risks increasingly shape regional financial security amid fiscal decentralisation and economic uncertainty. This study proposes a risk-integrated framework that incorporates budget imbalance, debt sustainability, revenue volatility, and contingent liabilities into a composite index. Using regional fiscal data from Uzbekistan, the results reveal an inverse relationship between fiscal risk exposure and financial security, demonstrating the analytical and policy value of a risk-oriented assessment approach.